Natural Law and Domestic Government in the Early Modern Period - Druwé, Wouter; Lesaffer, Randall; Sluijs, Geert (Early Modern History and Modern History E-Books online, Collection 2026., 2026)
Natural Law and Domestic Government in the Early Modern Period examines how natural law informed evolving ideas of governance from the sixteenth to eighteenth centuries. Through case studies spanning France, the Low Countries, England, Iberia, and colonial America, this volume explores how jurists, theologians, and political thinkers grappled with questions of sovereignty and justice. Contributors analyse influential figures from Bodin and Coke to Tuldenus and Lipsius, tracing how natural law intersected with legal concepts of rights, obligations, contracts, and associations. By uncovering diverse and contested uses of natural law, this collection offers a nuanced account of its enduring role in shaping early modern statecraft and political thinking. Contributors are: Marie Seong-Hak Kim, Rafael Cronje Mateus, Jeffrey Dymond, Pedro Ricardo da Silva Santos, Geert Sluijs, Paolo Astorri, Lars Cyril Nørgaard, Rosalind Acland, Carlos Pérez-Crespo, Signy Gutnick Allen, Sarah Limão Papa, and Alain Wijffels.